The Magic Orange Tree and other stories - "Gavin, Jamila" (Mammoth: London, 2000)
A collection of short stories celebrating the magic of children's imaginations. Monsters, dragons, giant birds, all types of mythical creatures are conjured up as excuses for dirtying clothes, missing tea or being late for school.
Keywords: Juvenile fiction